Physical practices as a way to improve the psycho-emotional state of students in a special medical group (A) - Minnikaeva, N.V.; Zashchirinskaya, O.V.; Brakamonte, N.A. Medina (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the impact of yoga, body-oriented creative techniques (BOCT) and breathing training on the correction of the psycho-emotional state of students in a special medical group. Methods and structure of the study. The experiment involved 126 1st- to 3rd-year students from a special medical group, aged 17 to 19 (Mage = 18.3; SD = 4.12; 87 young women and 39 young men). The study was conducted based on the method of M. Luscher (the colour choice method – MCC – as modified by L.N. Sobchik). Fisher’s criterion and rank statistics of the number of observations were used to process the quantitative data. Results and conclusions. The following methods were used in physical education classes with students from the special medical group: yoga, body-oriented creative techniques, and breathing exercises. Before and after classes, students from the special medical group laid out stimulus material (using the Luscher method) to assess their psycho-emotional state. Over a period of four months, physical education classes were conducted with students in an educational format. The structure of the class corresponded to the traditional model and included preparatory, main and final parts, with classes lasting from 45 to 60 minutes. The intensity of the psychophysical load during the classes did not exceed the requirements for health training based on an individual approach, taking into account the capabilities and limitations of each student. Throughout the classes, pedagogical control was exercised over the condition of the participants. Research has shown that all methods have a positive effect. Thus, after the classes, participants’ self-perception improved in terms of positive mood and good health. At the same time, the most positive changes were caused by the body-oriented creative technique based on dance and movement.